2019
DOI: 10.1042/bsr20180960
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of recombinant fructose-1,6-bisphosphatase gene mutations: evidence of inhibition/activation of FBPase protein by gene mutation

Abstract: Specific residues of the highly regulated fructose-1,6-bisphosphatase (FBPase) enzyme serve as important contributors to the catalytic activity of the enzyme. Previous clinical studies exploring the genetic basis of hypoglycemia revealed two significant mutations in the coding region of the FBPase gene in patients with hypoglycemia, linking the AMP-binding site to the active site of the enzyme. In the present study, a full kinetic analysis of similar mutants was performed. Kinetic results of mutants Y164A and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Twelve residues formed connections to all candidate ligands and the three references: Ala 24, Arg 140, Glu 29, Gly 21, Gly 26, Leu 30, Met 177, The 27, Thr 31, and Tyr 113. Of these 12, Met 177, Thr 31, and Tyr 113 are considered the most important residues due to their negative effect on the binding affinity when they are mutated [ 41 ]. Lys 112 is also among the key residues [ 41 ] and only missed interacting with C-0310.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Twelve residues formed connections to all candidate ligands and the three references: Ala 24, Arg 140, Glu 29, Gly 21, Gly 26, Leu 30, Met 177, The 27, Thr 31, and Tyr 113. Of these 12, Met 177, Thr 31, and Tyr 113 are considered the most important residues due to their negative effect on the binding affinity when they are mutated [ 41 ]. Lys 112 is also among the key residues [ 41 ] and only missed interacting with C-0310.…”
Section: Resultsmentioning
confidence: 99%
“…Of these 12, Met 177, Thr 31, and Tyr 113 are considered the most important residues due to their negative effect on the binding affinity when they are mutated [ 41 ]. Lys 112 is also among the key residues [ 41 ] and only missed interacting with C-0310.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent work by Topaz et al [45], published in Bioscience Reports extends our understanding of information transmission in mammalian FBPase. This study focused on seven variants: two which alter residues in a previously identified allosteric communication pathway and binding site for the allosteric inhibitor (4-(3-(6,7-diethoxy-quinazolin-4-ylamino)-phenyl)-thiazol-2-yl)-methanol (PFE; L56A and L73A); two affecting residues at the subunit interface (Y164A and M177A); two altering residues in the AMP binding site (K112A and Y113A) and one which changes a residue in a metal ion binding site (M248D).…”
Section: Getting the Message Acrossmentioning
confidence: 99%